Computer Science Research in India: A Scientometric Analysis of Research Output During the Period - Gupta, B.M.; Dhawan, S.M. (DESIDOC Journal of Library & Information Technology, 2003)
Computer science is of central importance to India for its impact on the national economy and society at large, and its role in shaping India as a technology superpower. This paper analyses the status of computer science research in India in terms of publication output, its areas of strength and weakness, and the leading institutions and individual scholars involved in computer science research in the country. http://dx.doi.org/10.14429/dbit.25.1.3644